Differences in the COMPUSTAT and Expanded Value Line Databases and the Potential Impact on Empirical Research - Kern, Beth B.; Morris, Michael H. (The Accounting Review, 1994)
[The Value Line Investment Survey has recently expanded its database of financial information on public firms from approximately 1,600 to over 4,000 companies to be more competitive in the financial database market. In addition, recent research (Philbrick and Ricks 1991) has shown that in determining earnings surprise, Value Line is a better source for actual EPS data. Since most research has been based on samples drawn from the COMPUSTAT database, increasing attention to the Value Line database leads one to question the effects of database choice on empirical research. One purpose of this study is to examine the differences in financial data between COMPUSTAT and Value Line along with the differences in the distribution of the size of firms between the two databases. Significant differences are found between COMPU-STAT and Value Line in the types of financial data reported for commonly used data items such as sales and total assets. In addition, the distribution of the size of firms in the databases has shifted over time. Prior to 1985 the bottom three quartiles of firms were significantly larger in Value Line. Beginning in 1985 the COMPUSTAT database had significantly larger firms across all quartiles. A second purpose is to demonstrate how the differences in the two databases can materially affect inferences about the population of firms. A study analyzing effective tax rates provides a good example because the use of the different databases produces very different results. This study extends prior research by examining which differences in the databases generate these different results. Much of the difference in the results is attributable to the different firms in the two databases. However, after controlling for common firms, the remaining significant differences can only be attributed to differences in the manner in which the financial accounting data are assimilated into the databases.]